2006
DOI: 10.1073/pnas.0601713103
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive evolution by mutations in theFLO11gene

Abstract: In nature, Saccharomyces yeasts manifest a number of adaptive responses to overcome adverse environments such as filamentation, invasive growth, flocculation and adherence to solid surfaces. Certain Saccharomyces wild yeasts, namely ''flor yeasts,'' have also acquired the ability to form a buoyant biofilm at the broth surface. Here we report that mutations in a single gene, identified as FLO11, separate these ''floating'' yeasts from their nonfloating relatives. We have determined that the capability to form a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
209
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(226 citation statements)
references
References 49 publications
8
209
0
5
Order By: Relevance
“…Similarly, the expression of FLO11 also confers hydrophobicity to yeast cells (Guo et al 2000;Reynolds and Fink 2001;Fidalgo et al 2006;Mortensen et al 2007;Govender et al 2008;Mulders et al 2009). Nevertheless, contradictory results regarding the flocculation behaviour of FLO11 transformants have been presented.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the expression of FLO11 also confers hydrophobicity to yeast cells (Guo et al 2000;Reynolds and Fink 2001;Fidalgo et al 2006;Mortensen et al 2007;Govender et al 2008;Mulders et al 2009). Nevertheless, contradictory results regarding the flocculation behaviour of FLO11 transformants have been presented.…”
Section: Discussionmentioning
confidence: 99%
“…Its regulation is very complex, with many different inputs and pathways affecting FLO11 expression (Madhani and Fink 1997;Rupp et al 1999;Heitman 2000, 2002;Kohler et al 2002;Kuchin et al 2002;Braus et al 2003;Zeitlinger et al 2003;Halme et al 2004;van Dyk et al 2005;Bumgarner et al 2009;Octavio et al 2009). We have previously described that a high level of FLO11 expression is required for the formation of a liquid surface biofilm (Fidalgo et al 2006). Moreover, we showed that only the promoter carried by the "flor" Saccharomyces yeast strain (used to produce sherry wine) is able to reach this level of expression.…”
mentioning
confidence: 73%
“…To directly address these possibilities, we first examined the effect of deleting RPD3 on FLO11 expression in both flor (133d) (Fidalgo et al 2006) and laboratory (L5684) strains. Given possibility (iii), we also examined the effect of deleting other candidate deacetylases (HOS1, HOS2, HOS3, and HDA1).…”
Section: Flo11 Transcriptional Activation Exhibits An Allele-specificmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell morphology and growth habit of budding yeast have been the target of genetic studies in laboratory strains (Jorgensen et al 2002;Pruyne et al 2004;Ohya et al 2005;Moseley and Nurse 2009) and environmental isolates (Yvert et al 2003;Fidalgo et al 2006;Nogami et al 2007;Granek and Magwene 2010), but the genetic underpinnings of many naturally occurring yeast morphologies remain unknown. In analysis of the genetic basis of varying traits in yeast, a recently reported population genomic data set (Liti et al 2009) established a powerful test bed for the candidate gene approach.…”
mentioning
confidence: 99%